Construction of an Unmarked Zymomonas mobilis Mutant Using a Site-Specific FLP Recombinase - Shao-Lan Zou; Jie-Fang Hong; Cui Wang; Xin Jing; Min-Hua Zhang (Food Technology and Biotechnology, 2012)
Flippase expression was carried out in Zymomonas mobilis strain ZM4. The FRT-flanked selection marker gene was first integrated into the ZM4 chromosome by homologous recombination. The Saccharomyces cerevisiae flp gene was then introduced under the control of the ZM4 gap gene promoter (Pgap, encoding glyceraldehyde-3-phosphate dehydrogenase) or the λ bacteriophage cI857-pR contained in the broad-host-range cloning vector pBBR1-MCS-2. This study demonstrated that flp was expressed and that the deletion frequency of the FRT-flanked marker gene was very high (approx. 100 %). In addition, the flp gene expression vector could be conveniently removed from the resulting unmarked Z. mobilis mutants by serially transferring the cells three times into antibiotic-free medium, thereby establishing an efficient method for constructing unmarked Z. mobilis mutants.